Assessment of the complications after percutaneous fixation with cannulated cancecellous screws among the cases of tibial plateau fractures in a tertiary healthcare institute: a cross sectional study - Bagul, Joti P.; Dole, Pankaj P. (International Journal of Research in Orthopaedics, 2020)
Background: Fractures in the tibial plateau were first defined as car bumper fractures. Tibial plateau fractures are a diverse group of fractures that reflect a wide range of intensity, ranging from simple accidents to intricate fracture trends that test even the most qualified surgeons. The present study was conducted to study the result of minimally invasive technique for tibial plateau fractures by percutaneous fixation with cannulated cancellous screws and to study complications associated with it in a tertiary care center. Methods: It was a cross sectional study conducted among 13 patients with tibial plateau fractures during January 2016 to December 2016 admitted under department of orthopedics in a tertiary healthcare institute in northern Maharashtra. The criteria for selection of a case were a fracture of tibial plateau (Shatzker’s type I to type IV) with displacement or depression more than 8mm. Results: One patient (7%) had compartment syndrome at the time of presentation. No patient in our series had early postoperative complication. One patient developed knee joint pain 16 months after operation due to early osteo-artgritic changes. Conclusions: There was no early complication related to surgery like superficial or deep infection, damage to neurovascular structures, etc. Ten patients (76%) achieved full range of knee motion within 3 months after operation. All the fractures were united within 14 weeks duration.